2020
DOI: 10.1007/s40519-020-00857-z
|View full text |Cite
|
Sign up to set email alerts
|

Rumination, mood, and maladaptive eating behaviors in overweight and healthy populations

Abstract: Purpose The literature suggests that rumination (i.e., repetitive thinking about 1 or more negative concerns that is perceived as difficult to control) is linked to impaired emotional regulation and increases negative affect. Not only individuals suffering from overweight or obesity, but also healthy individuals might use emotional eating as a coping strategy to deal with negative affect caused by rumination. The aim of the present study was to determine the link between rumination and maladaptive eating strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(107 reference statements)
0
16
0
2
Order By: Relevance
“…This type of data is burdened with the problem of self-presentation of the respondents and lack of possibility of objective verification. Finally, although snacking (based on a single item) has been shown to be predictive of related behaviours in our previous research [ 71 ] it should be emphasized that in the present study we used the subscale that have not been validated in Polish population.…”
Section: Discussionmentioning
confidence: 99%
“…This type of data is burdened with the problem of self-presentation of the respondents and lack of possibility of objective verification. Finally, although snacking (based on a single item) has been shown to be predictive of related behaviours in our previous research [ 71 ] it should be emphasized that in the present study we used the subscale that have not been validated in Polish population.…”
Section: Discussionmentioning
confidence: 99%
“…These studies all showed greater NA at the time of perceived binge eating (40,41) or emotional eating (42).…”
Section: Studies Examining Concurrent Associations Between Na and Locmentioning
confidence: 88%
“…Three EMA studies used designs that made it difficult to disambiguate whether NA was an antecedent or consequence of LOC (e.g., designs that asked about affect and LOC concurrently). These studies all showed greater NA at the time of perceived binge eating ( 40 , 41 ) or emotional eating ( 42 ).…”
Section: Research Examining Patterns Of Na Surrounding Loc In Daily Lifementioning
confidence: 91%
“…Further, in community‐based samples, between‐day analyzes revealed that greater negative affect is associated with increased emotional eating (Haedt‐Matt et al, 2014; Klump, Keel, Burt, et al, 2013; Klump, Keel, Racine, et al, 2013). However, not all EMA studies have consistently supported a link between fluctuations in negative affect and emotional eating (Boh et al, 2016; Kornacka et al, 2021). For example, Kornacka et al (2021) found that state negative affect (operationalized by self‐report ratings of current emotional state on six‐point scales ranging from content to discontent and well to unwell) was less predictive of daily emotional eating than rumination.…”
Section: Introductionmentioning
confidence: 99%